Analysis of WhatsApp Business Features on the Effectiveness of Marketing Communications for Craft MSMEs in Jambi City - Rudi Nata; Ari Andrianti; Miranty Yudistira; Oki Dahwanu; Rahmad Ashar; Renaldi Yulvianda (SISTEMASI, 2026)
This study analyzes the influence of WhatsApp Business features (Broadcast Message, Quick Reply, Catalog, and Labeling) on marketing communication effectiveness among creative SMEs in Jambi City. Using a mixed methods approach, the results indicate that WhatsApp Business features collectively have a significant effect on marketing communication effectiveness (R² = 0.596, p = 0.003), explaining 59.6% of the variance. Among the four features, only the Catalog feature showed a significant positive influence (β = 0.903, p = 0.034), highlighting its critical role in enhancing customer communication and engagement. The novelty of this research lies in its focus on creative SMEs producing cultural heritage based products in Jambi and its simultaneous evaluation of four key WhatsApp Business features. The findings suggest that SMEs should prioritize optimizing Catalog features through high quality visual content that effectively communicates product value and local cultural identity, while policymakers should support targeted digital literacy programs for heritage based businesses.